Pleistocene Fossil Turtles (Testudinoidea, Cryptodira) from the Talara Tar Seeps, Peru - Deza, Anthony (2019)
A description of Pleistocene fossil turtles discovered in the Talara Tar Seeps, Tablazos deposits of the northern coast of Peru is provided in this paper. The specimens are mostly fragmentary plates of carapaces and plastra of turtles belonging to two cryptodiran families of the superfamily Testudinoidea, identified to genus level based on measurements and comparisons with extant and fossil taxa and identification of mosaic diagnostic features. Turtles of the Geoemydidae family are the most abundant, with fossil remains attributed to Rhinoclemmys (indeterminate species). Less abundant fossil remains belong to the Testudinidae, with specimens attributed to the genus Chelonoidis (indeterminate species). These fossils show that the northern coast of Peru had ecosystems that supported abundant aquatic and terrestrial turtles (tortoises) during the Pleistocene in areas where they are completely absent today.